Hydrologic and biotic control of nitrogen export during snowmelt: a combined conservative and reactive tracer approach - Petrone, K; Buffam, I; Laudon, H (Water resources research, 2007)
1 Dissolved inorganic nitrogen (DIN) and dissolved organic nitrogen (DON) stored in the snowpack are important sources of N in snow-covered ecosystems, yet we have limited knowledge of their fate during the melt period. Our objective was to quantify the role of hydrologic and biogeochemical processes in regulating stream fluxes of DIN (NO3(-) + NH4(+)) and DON in a forest-dominated and a wetland-dominated catchment during the snowmelt period. We combined isotopic hydrograph separation with concurrent measurements of meltwater DIN and DON to calculate "conservative" N export (hydrologic mixing only) and compared it with "reactive" N export (i.e., observed fluxes that include biogeochemical processes). On balance, N was retained in the catchments during snowmelt because of storage of meltwater N in soils, but our N export comparison revealed N generation (mostly as DON) from the mobilization of dissolved organic matter. In contrast, NO3(-), which was highly enriched in snowpack meltwater, remained below detection in streams, and both catchments were sinks for NO3(-), suggesting that denitrification and/or uptake may be important at the catchment scale. Over the melt period, the forest catchment was a greater total N source because of the convergence of lateral flow and near-stream riparian N sources in surface soils, which elevated stream DON and to a lesser extent NH4(+). In contrast, preferential flow in the wetland catchment tended to dilute DIN in saturated peatland soils and in the stream, whereas DON varied little over time. These findings highlight the importance of hydrologic processes that store meltwater N in catchment soils but at the same time deliver DON from riparian sources to the stream. Further, model results suggest that biotic uptake and/or sorption effectively retain much of the meltwater DIN from the snowpack. Collectively, hydrologic storage and biogeochemical processes act to retain N that is likely important for boreal ecosystem production later in the spring and summer seasons.